Pengaruh kualitas pelayanan dan nilai pelayanan administrasi akademik terhadap kepuasan mahasiswa fakultas ekonomi dan bisnis universitas mulawarman - Vinci Atmadinata; Adam Idris; Santi Rande (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this study was conducted to determine and analyze the Influence of Service Quality And Value Satisfaction Services Academic Administration Faculty of Economics and Business, University of Mulawarman. This study uses Partial Least Square (PLS) which can be used on any kind of scale of data (nominal, ordinal, interval, ratio) and assuming a more flexible terms. PLS is one of the Structural Equation Modeling (SEM) capable of analyzing latent variables, indicator variables and measurement error directly, the samples are 98 students of the Faculty of Economics and Business, University of Mulawarman. he results showed the influence of service quality on student satisfaction through value generated path coefficient value of 0.244 and t p value of 2.155 and 0.032. While the influence of the value of service to satisfaction of students through path coefficient value of 0.442 and t p value of 3.726 and 0.000. And impact of service quality and value of service to satisfaction of students simultaneously generated value Fh of 6126 with R square of 0338, so it can be concluded that the quality of service and the value of service has a significant influence on student satisfaction either partially or simultaneously.Keywords: Service Quality, Service Value, Satisfaction